Endothelial Glucocorticoid Receptor Suppresses Atherogenesis—Brief Report. Issue 4 (April 2015) - Goodwin, Julie E.; Zhang, Xinbo; Rotllan, Noemi; Feng, Yan; Zhou, Han; Fernández-Hernando, Carlos; Yu, Jun; Sessa, William C.
<x xml:space="preserve">Abstract</x> Objective— The purpose of this study was to determine the role of the endothelial glucocorticoid receptor in the pathogenesis of atherosclerosis. Approach and Results— Control mice and mice lacking the endothelial glucocorticoid receptor were bred onto an Apoe knockout background and subjected to high-fat diet feeding for 12 weeks. Assessment of body weight and total cholesterol and triglycerides before and after the diet revealed no differences between the 2 groups of mice. However, mice lacking the endothelial glucocorticoid receptor developed more severe atherosclerotic lesions in the aorta, brachiocephalic artery, and aortic sinus, as well as a heightened inflammatory milieu as evidenced by increased macrophage recruitment in the lesions. Conclusions— These data suggest that the endothelial glucocorticoid receptor is important for tonic inhibition of inflammation and limitation of atherosclerosis progression in this model.